A Comparative Study between Early Versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis in a Tertiary Care Center of Nepal - Koirala, Ashok; Shah, Ram Sagar; Shah, Sachidanand; Adhikari, Dinesh; Bhattarai, Amit; Niraula, Richa; Yadav, Ajay Kumar (Journal of Nobel Medical College, 2022)
Background: Laparoscopic Cholecystectomy is considered as a gold standard treatment for symptomatic cholelithiasis. The timing of surgery for acute Cholecystitis is still controversial, weather to go early surgery or wait for six to eight weeks after conservative management. Therefore, the aim of this study is to compare the clinical outcomes of early versus delayed laparoscopic cholecystectomy for acute Cholecystitis.Materials and Methods: A prospective study was conducted in Nobel Medical College Teaching Hospital, Biratnagar, Nepal. Total of 80 patients with the diagnosis of acute Cholecystitis were enrolled in the study. The patients were equally divided in two groups: 40 underwent early laparoscopic cholecystectomy within 72 hours of admission (Group A) and next 40 underwent delayed laparoscopic cholecystectomy after 6-8 weeks of conservative management (Group B).Results: Out of 80 patients of acute Cholecystitis, mean age of the patients in Group A was 43.40±13.45 years and that in Group B was 44.80±14.36 years. The mean operative time in Group A was 90.22±2.81 minutes whereas in Group B it was 80.97±4.47 minutes. Mean duration of Hospital stay in Group A was 2.02±0.15 days whereas in Group B it was 2.15±0.36 days. Two patients in Group A and one patient in Group B converted to open cholecystectomy. Three patients of Group A and one patient of Group B landed in outpatient department with superficial surgical site infection.  Group B patients underwent second hospital admission compared to Group A patients.Conclusion: Early Laparoscopic cholecystectomy for acute cholecystitis is almost comparable with delayedLaparoscopic cholecystectomy. However, early laparoscopic cholecystectomy reduces the morbidity of patients as well as it is cost-effectiveness.